Interface between Subalternity and Sexuality in Arundhati Roy’s The God of Small Things - Dhakal, Sedunath (KMC Research Journal, 2019)
There is an interface between subalternity and sexuality in Arundhati Roy’s ‘The God of Small Things’. This article attempts to describe that sexuality has been stood as a form of protest and resistance against all forms of discrimination and prejudices against subaltern groups. The central characters of the novel, Velutha, and Ammu’s copulation with each other is implicitly an attempt to break the artificial and arbitrary walls constructed between the so called elite class and the subaltern groups. Thus, the sexuality can be discussed as a means of liberation from the chain of subalternity. However, the attempt was averted when the protesters (Velutha and Ammu) confront the mechanical society. The act of copulation exposed the subalternity of Velutha and sexuality of Ammu. Both Ammu and Velutha cross the social boundary. So called marriage system and love laws both have been transgressed upon. It is due to the sexual act, the so called authentic laws and systems have been broken, all things dismissed, impossible become possible. Such instinct is uncontrollable. This article analyses that in the matter of sex, so called touchable and untouchable, master and servant, so called higher class and lower caste all become equal; there remains no boundary at all; as it has been presented in Arundhati Roy’s The God of Small Things.